Damage mapping with a degrading elastic modulus using piezospectroscopic coatings. (October 2015) - Freihofer, Gregory; Schülzgen, Axel; Raghavan, Seetha
Abstract: The development of piezospectroscopic (PS) composites has enabled the creation of a non-destructive evaluation (NDE) technique which integrates piezospectroscopy, digital image correlation (DIC) and analytical multi-scale mechanics to map the elastic modulus of a coated material. The measured elastic modulus was represented as a normal distribution with a mean value (32.2 GPa) which is within 8% of the conventionally recorded modulus (35 GPa). Damage mechanics are applied to map elastic degradation in situ mechanical loading with an average uncertainty ( 10 GPa) that was sufficient in observing subsurface, progressive damage patterns which are unique to the coated material. Abstract : Graphical abstract: Abstract : Highlights: Multi-scale mechanics, DIC and PS were combined to create a new NDE technique. A mean elastic modulus was calculated within 8% of conventional methods. Damage was evaluated with degrading elastic modulus maps in situ mechanical loading.